On the economic causes of the present state of agriculture in Ireland: part four - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1849)
In my last paper on the Economic Causes of the State of Agriculture in Ireland, I noticed three of the six legal impediments to the application of capital, by tenants, to agricultural operations, namely the old feudal principle that the ownership of improvements follows the ownership of the land, the law of agricultural fixtures, and the restraints on leasing power. In this paper I propose to notice the other three impediments, namely, the restraints on the power of making tenant-right agreements, the stamps on leases and other contracts with tenants, and the remnant of the usury laws. I shall also consider the legal impediments to the application of capital, by proprietors, to agricultural improvements.
Read January 29th 1849
Keywords: Tenant rights; Stamp duty; 314.15